Diseño de un sistema de gestión de la seguridad de la información (SGSI) basado en la norma ISO 27001:2013 para la red corporativa de la empresa Ecuatronix. - Villacís Espinosa, Miguel Leopoldo (2016)
This graduation project is part of the design of an information security management system based on ISO / IEC 27001: 2013 for Ecuatronix Co. The starting point was to know the update of the ISO / IEC 27001: 2013 to reflect the new control objectives and controls to be implemented, then it continued with the reconnaissance of company to define the information assets, and have found threats or attacks that can be victims as well as a risk analysis was also performed to define the criteria for mitigating them. The system development was did through the process architecture called PDCA, considering that the analysis is conducted using estimation qualitative risk – Triple Criteria Method - PGV, which leads to define a range of threats that have been divided into three groups that are human, technological and natural hazards. Finally this project contains several tables that detailing important information to be taken into account the most important will be those in which the application of controls is evident, and two simulations of a new local area network and a corporate network that will unify the main office with its branches, this network will be voice and data.